(untitled) (Journal of Educational Sciences, 2018)
The article deals with the problems of interference of the native language of foreigners in the production of simple sentences in Russian. The ability to correctly construct a sentence in accordance with the realities of the studied language is considered as one of the ways of representing language communication in action. In order to achieve the ultimate goal of learning, namely, the free knowledge of a foreign language, it is necessary to determine what and why negatively affects the learning process of foreign language communication, as well as what can be done to obtain a positive result. The authors made a comparative survey of the structures of the simple sentences, the influence of word order on the meaning of the utterance in Chinese, Korean, Japanese, Turkish, Russian languages on the basis of textbooks on the grammar of these languages, articles on comparative grammar and taking into account the mistakes made in written and oral work in the Russian language to foreign students. In this article, the authors determine the range of the most obvious causes of mistakes of foreign students in the structure of the proposal. The article analyzes the causes of psychological discomfort when changing the order of words, intonation, emotionality in speech in Russian. Examples of the influence of “language formulas” and culturological elements of the native language on the mastery of a foreign language, in this case the Russian language, are presented. The relevance of this topic lies in the usefulness of this kind of research, in terms of linguistic teaching. Key words: interference, the structure of a simple sentence, a native language, a foreign language, word order, language communication, cultural features.